Elevated n-3/n-6 PUFA ratio in early life diet reverses adverse intrauterine kidney programming in female rats - Voggel, Jenny; Fink, Gregor; Zelck, Magdalena; Wohlfarth, Maria; Post, Julia M.; Bindila, Laura; Rauh, Manfred; Amann, Kerstin Ute; Alcazar, Miguel A. Alejandre; Doetsch, Joerg; Nuesken, Kai-Dietrich; Nuesken, Eva (Journal of Lipid Research, 2022)
Intrauterine growth restriction (IUGR) predisposes to chronic kidney disease via activation of proinflammatory pathways, and omega-3 PUFAs (n-3 PUFAs) have anti-inflammatory properties. In female rats, we investigated 1) how an elevated di-etary n-3/n-6 PUFA ratio (1:1) during postnatal kidney development modifies kidney phospholipid (PL) and arachidonic acid (AA) metabolite content and 2) whether the diet counteracts adverse molecular pro-tein signatures expected in IUGR kidneys. IUGR was induced by bilateral uterine vessel ligation or intra-uterine stress through sham operation 3.5 days before term. Control (C) offspring were born after uncom-promised pregnancy. On postnatal (P) days P2-P39, rats were fed control (n-3/n-6 PUFA ratio 1:20) or n-3 PUFA intervention diet (N3PUFA; ratio 1:1). Plasma parameters (P33), kidney cortex lipidomics and pro-teomics, as well as histology (P39) were studied. We found that the intervention diet tripled PL-DHA content (PC 40:6; P < 0.01) and lowered both PL-AA content (PC 38:4 and lyso-phosphatidylcholine 20:4; P < 0.05) and AA metabolites (HETEs, dihydrox-yeicosatrienoic acids, and epoxyeicosatrienoic acids) to 25% in all offspring groups. After ligation, our network analysis of differentially expressed proteins identified an adverse molecular signature indicating inflammation and hypercoagulability. N3PUFA diet reversed 61 protein alterations (P < 0.05), thus miti-gating adverse IUGR signatures. In conclusion, an elevated n-3/n-6 PUFA ratio in early diet strongly reduces proinflammatory PLs and mediators while increasing DHA-containing PLs regardless of prior intrauterine conditions. Counteracting a proin-flammatory hypercoagulable protein signature in young adult IUGR individuals through early diet intervention may be a feasible strategy to prevent developmentally programmed kidney damage in later life.
CRIS-Team WoS Importer:2022-12-02